2020
DOI: 10.3390/nu12061839
|View full text |Cite
|
Sign up to set email alerts
|

Palatable Noodles as a Functional Staple Food Made Exclusively from Yellow Peas Suppressed Rapid Postprandial Glucose Increase

Abstract: Legumes are low-carbohydrate food and are abundant in dietary fiber. In order to provide a functional staple food that does not cause a rapid increase in postprandial blood glucose levels, four kinds of legumes were focused on as ingredients. Noodles made from dehulled yellow pea, unshelled yellow pea, chickpea, and lentil were prepared and evaluated as functional staple foods for controlling blood glucose via an in vitro digestion method. We also measured breaking stress and breaking strain using a creep mete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
(41 reference statements)
1
16
0
1
Order By: Relevance
“…From the results of the afternoon work, the intervention session showed a statistically significant lower average blood glucose level, blood glucose AUC, and blood glucose Cmax compared to the control session. The legume-based noodles used in this study were proven to be low GI in a previous study, so these results are consistent with it ( 32 ).…”
Section: Discussionsupporting
confidence: 90%
“…From the results of the afternoon work, the intervention session showed a statistically significant lower average blood glucose level, blood glucose AUC, and blood glucose Cmax compared to the control session. The legume-based noodles used in this study were proven to be low GI in a previous study, so these results are consistent with it ( 32 ).…”
Section: Discussionsupporting
confidence: 90%
“…soluble fibre (pectin, gum and mucilage), insoluble fibre (mainly cellulose and hemicellulose) and α‐galactose derivatives of sucrose (mainly raffinose that with prebiotic and immune‐stimulating effects, stachyose and verbascose) (Clemente & Olias, 2017; Sozer et al ., 2017). Meanwhile, the fibre cannot be digested and absorbed, which is beneficial to control the rise of postprandial glycaemic (Yoshimoto et al ., 2020). In addition, carbohydrates also include monosaccharides and oligosaccharides; and compared with monosaccharides, oligosaccharides in legumes are not easily digested by humans (Hall et al ., 2017).…”
Section: Nutritional Properties and Physiological Functions Of Legume...mentioning
confidence: 99%
“…Although rice noodles are a high GI food and have poor quality, PulseON® is a new type of chickpea flour being rich in RS and dietary fibre, adding chickpea flour to rice noodles is well‐liked by people with T2DM and significantly lowers its GI (Sofi et al ., 2020a, 2020b; Delamare et al ., 2020). Additionally, extruded rice noodles made with yellow peas are a low GI food, which can also control glycaemic levels and be beneficial for people with T2DM (Yoshimoto et al ., 2020). Furthermore, Wee & Henry, 2020 have shown that ERPs supplemented with different concentrations of protein, polysaccharide and lipid all incarnate a lower GI, which is beneficial to alleviate the phenomenon of increasing diabetes incidence in Asia.…”
Section: Nutritional Properties and Physiological Functions Of Legume...mentioning
confidence: 99%
“…Cold extrusion is an ideal process to produce pasta fortified with legumes, although this fortification is a new process. The principal studies in the literature showed the fortification of wheat flour with legumes such as soya, pea, lentil, chickpea, lupin and bean [ 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 ]. These authors revealed the modifications observed in the pastas fortified in comparison to the control pasta (in general, durum wheat semolina).…”
Section: Effect Of Cold Extrusion On the Bioactive Compounds Of Pumentioning
confidence: 99%